Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa SD Negeri Sumbermulyo 01 dalam Pembelajaran Daring - tri fone pamungkas; Ika Oktavianti; Sekar Dwi Ardianti (Journal Prakarsa Paedagogia, 2021)
This study aims to analyze parenting styles on learning motivation of Sumbermulyo 01 elementary school students in online learning. This research uses descriptive qualitative research methods. The data collection technique used in this study was data triangulation, namely observation, in-depth interviews and documentation. The subjects studied were students, parents and teachers of Sumbermulyo elementary school. The data analysis technique used is data reduction, data presentation and conclusion. The results showed that parents provided a form of democratic parenting for their children during online learning, in the sense of giving children the freedom to play at certain times and continue to carry out online learning and do assignments according to a mutually agreed schedule. Student motivation in online learning is good even though it fluctuates according to the child's condition at a certain time. Democratic parenting patterns have a good impact on the child's or student's psychological condition during online learning, besides that the teacher also provides motivation to students and guidance to parents during online learning.